COMPUTER MODELING OF ION-EXCHANGE PROCESSES WITH APPLICATION TO HYDROGEOCHEMICAL PROBLEMS - Solomini G.A.; Krainov S.R. (My University, 2004)
Based on the analysis of published data, results of experimental investigations, and computer simulation, the constants of ion exchange reactions on clay minerals were determined and the factors affecting these constants were established. This information was applied to the solution of typical hydrogeochemical problems including (a) the calculation of concentrations of absorbed cations in clay, (b) the determination of the equilibrium compositions of water and clay, and (c) the evaluation of the role of ion exchange in the geochemical evolution of HCO3-Ca groundwater and water of the HCO 3-Na composition. For the solution of these problems, we used observations on real changes in the chemical compositions of groundwater in the Moldavian artesian basin.